Development of a Spatially Resolved Optical Technique to Measure Temperature using Two-Photon Absorption of Xenon - Bednar, Natalie J. (My University, 2005)
A new spatially resolved optical technique to measure temperature was developed using two-photon absorption of xenon. This experiment excited the 256 nm two-photon transition of xenon by focusing the excitation source into a test cell at room temperature. Two-photon absorption only occurs at the focus of a laser beam; therefore a point measurement technique was possible. The spatial resolution for this experiment was approximately 0.6 mm; however, this technique enables higher resolution depending on the focus of the laser beam. Two-photon absorbance versus xenon number density was determined experimentally and used to validate a theoretical model created in MATLAB. This technique was designed primarily for two non-reacting flows: the vortex tube and the pulse tube. A case study for measurement in a vortex tube was presented; however, applying this technique to a pulse tube will be similar.
Under the supervision of Assistant Professor Scott T. Sanders, Pages: 95
Keywords: University of Wisconsin--Madison. College of Engineering.; Thesis (M.S.)--University of Wisconsin--Madison, 2005.